2007
DOI: 10.1021/es062908g
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxylated Metabolites of β- and δ-Hexachlorocyclohexane:  Bacterial Formation, Stereochemical Configuration, and Occurrence in Groundwater at a Former Production Site

Abstract: Although the use of hexachlorocyclohexane (HCH), one of the most popular insecticides after the Second World War, has been discontinued in many countries, problems remain from former production and waste sites. Despite the widespread occurrence of HCHs, the environmental fate of these compounds is not fully understood. In particular, environmental metabolites of the more persistent beta-HCH and delta-HCH have not been fully identified. Such knowledge, however, is important to follow degradation and environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 28 publications
6
64
0
Order By: Relevance
“…Additionally, a linX gene, encoding a protein that has activity similar to that of linC (but probably is not involved in the degradation pathway of γ-HCH), was also characterized 7 . Recent studies have shown that both LinA and LinB are also involved in the degradation of the recalcitrant β-and δ-HCH isomers [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a linX gene, encoding a protein that has activity similar to that of linC (but probably is not involved in the degradation pathway of γ-HCH), was also characterized 7 . Recent studies have shown that both LinA and LinB are also involved in the degradation of the recalcitrant β-and δ-HCH isomers [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…However, these metabolites were not formed when δ-HCH was incubated in presence of LinB. Further studies revealed that D3 and D4 were not formed in δ-HCH degradation via D1 and D2 respectively but from δ-PCCH (formed by dehydrochlorination of δ-HCH by LinA) as a result of hydrochlorination reaction by LinB [9] (Fig. 7).…”
Section: Evolution Of Lin Genes To Perform Newer Function In B90amentioning
confidence: 94%
“…Studies on the degradation of β-and δ-HCH with purifi ed LinB from E. coli revealed that these isomers are hydroxylated to form pentachlorocyclohexanols (B1 and D1) and tetrachlorocyclohexandiols (B2 and D2) [62]. Subsequent studies have confi rmed the formation of B1 and B2 from β-HCH and D1 and D2 from δ-HCH in a resting cell assay of strain B90A [9] (Figs. 6, 7).…”
Section: Evolution Of Lin Genes To Perform Newer Function In B90amentioning
confidence: 95%
See 1 more Smart Citation
“…Aerobic biodegradations of HCHs in soil are well investigated for the bacteria Sphingomonadaceae (Pal et al 2005). Degradation of HCHs is enabled by the exoenzymes LinA and LinB (Nagata et al 1999;Suar et al 2005;Raina et al 2007;Bala et al 2012;Geueke et al 2013). Degradation thereby forms isomer-specific metabolization products such as pentachlorocyclohexene for a-HCH and c-HCH and pentachlorocyclohexane-1-ol for b-HCH and d-HCH.…”
Section: Soil Samples and Percolationmentioning
confidence: 99%